Symptom reporting and body-related subjectivity among women and men (Italian Journal of Public Health, 2006)
The main purpose of this paper is to explore whether there are differences between men and women in bod-ily consciousness, bodily dissatisfaction and state of affect and if these differences contribute to gender dif-ferences in the reporting of symptoms. A questionnaire was sent out to a randomly selected sample of 1500persons, between the ages of 25-55 years in Sweden. The results showed that women in this sample weremore dissatisfied with their bodies, had higher body awareness and scored higher on the measure of nega-tive affect than men. When considering body consciousness and body esteem in combination with negativeaffect, the difference between men and women in symptom reporting was reduced, although a considerablegender difference in symptom reporting remained unexplained.
Keywords: symptom reporting; differences between men and women; body esteem; body awarenes; negative affect